"You have to trust yourself": The Overlooked Role of Self-Trust in Coping with Chronic Illness - Grob, Rachel (The Hastings Center report, 2023)
Self-trust is essential to the well-being of people with chronic illnesses and those who care for them. In this exploratory essay, we draw on a trove of health narratives to catalyze examination of this important but often overlooked topic. We explore how self-trust is impeded at both personal and structural levels, how it can best be nourished, and how it is related to self-advocacy. Because people's ability to trust themselves is intrinsically linked to the trust others have in them, we pay particular attention to the role that allies such as clinical professionals play in the development of self-trust, highlighting the importance of eliciting patient narratives, of curious listening, and of compassionately raising questions. We also contrast the self-trust paradigm with that of self-management, which tends to replace the former's attention to patients’ experiences, abilities, qualities, or judgments with a professionally dominated discourse dedicated to addressing illness through behavior changes prescribed by clinicians. We close with a call to action, exhorting readers to focus on supporting self-trust in health care settings and on creative research in this critical yet heretofore underrepresented domain.